The Impact of Internal Advertising in the Markets and Malls on Saudi Women Purchasing Decision - Al Ammari, Haifa Abdullah; Albalboushi, Abdul Radhi Hamdi (Journal of Humanities & Social Sciences, 2019)
The study aimed to identify the internal advertising in markets and commercial malls and its impact on the Saudi women purchasing decision, it also relationship between the exposures to the internal adverting and making the purchase decision. The researcher used the descriptive approach that is based on the field survey through responding to the study questionnaire, which was distributed to the study sample amounted 300 students from King Saud University.The study results revealed that the internal advertising effects on the purchasing decision of the respondents by (75.5%). The result of the study shows that the majority of the respondents are positively affected. This means that the internal advertising makes the study sample buy the advertised products or to be convinced. It also found that there is no relationship between increasing the exposure to the internal advertising and the purchase decision.The researcher recommended the need to design an attractive advertisings that take into consideration the innovation and technical standards to attract the consumer and urge him to follow the content, and stresses at the same time the need to find scientific control specialized to examine the advertising on the basis of standards of honesty and not to exaggerate before presenting it.
Keywords: internal advertising; promotion; purchase decision; Saudi women